Fabrication of graphene transistor in a microfluidic channel. - Govindharajulu Priya. (2013)
Micro fluidics is an attractive area of research due to its unique properties at small scale as well as providing a path to analyze the samples precisely by reducing the need for laboratory procedures. Hence, microfluidic devices are commonly known as “Lap on Chip” devices. Additionally, discovery of graphene in 2004, which is a two-dimensional allotrope of carbon, brought new concepts and applications in biology as well as semiconductor industry to overcome the limitations of silicon based operations. The main focus of this thesis work is to integrate microfluidics with graphene nanomaterial and utilizing the highly expressed trans membrane proteins called EPCAM (Epithelial cell adhesion molecule) biomarkers or antigens in Huh 7 liver cancer cell line that causes dramatic changes in the conductance or Dirac point in the Graphene Field Effect